2001
DOI: 10.1095/biolreprod65.4.1127
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Conventional Controlled-Rate Freezing and Vitrification on Morphology and Metabolism of Bovine Blastocysts Produced In Vitro1

Abstract: This study compares the effects of conventional controlled-rate freezing and vitrification on the morphology and metabolism of in vitro-produced bovine blastocysts. Day 7 expanded blastocysts cultured in synthetic oviduct fluid with 5% fetal calf serum were frozen in 1.36 M glycerol, 0.25 M sucrose or vitrified in 25% glycerol, 25% ethylene glycol. Cell alterations and in vitro development were evaluated immediately after thawing or after 72 h. The effect of cryopreservation on inner cell mass and trophectoder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
1
6

Year Published

2002
2002
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(39 citation statements)
references
References 52 publications
3
29
1
6
Order By: Relevance
“…The average respiration rate of day 7 blastocysts, measured by the microsensor system, was in accordance with the results obtained by Overströ m (1996), using in vivo day 7 bovine blastocysts (1.47^0.44 nl/h). On the other hand, our results for day 7 embryos were considerably lower than those documented by Donnay & Leese (1999), Kaidi et al (2001) and Shiku et al (2001), but their studies were performed on day 8 blastocysts, containing higher number of cells and larger diameters. Differences between our data and those of Thompson et al (1996) can also be explained by the different blastocyst stage (day 7 versus day 6) used in these two experiments.…”
Section: Discussioncontrasting
confidence: 92%
“…The average respiration rate of day 7 blastocysts, measured by the microsensor system, was in accordance with the results obtained by Overströ m (1996), using in vivo day 7 bovine blastocysts (1.47^0.44 nl/h). On the other hand, our results for day 7 embryos were considerably lower than those documented by Donnay & Leese (1999), Kaidi et al (2001) and Shiku et al (2001), but their studies were performed on day 8 blastocysts, containing higher number of cells and larger diameters. Differences between our data and those of Thompson et al (1996) can also be explained by the different blastocyst stage (day 7 versus day 6) used in these two experiments.…”
Section: Discussioncontrasting
confidence: 92%
“…This value is closer to the value of 0.14 £ 10 213 moles/s for bovine morula reported by Shiku et al (2001) than for values reported by Thompson et al (1996) of , 9 £ 10 211 moles/s for bovine embryos from day 0 -4 of culture. Reported values for bovine blastocysts range from 0.4 -1.5 £ 10 29 moles/s , Kaidi et al 2001, Donnay et al 2002. Reasons for the differences in absolute amounts are not known but could include methodology since the lower values in the present study and by Shiku et al (2001) are based on electrochemical measurements of oxygen, while other papers cited above rely on quenching of pyrene fluorescence by oxygen.…”
Section: Discussionmentioning
confidence: 99%
“…Embryos transferred fresh included unexpanded and expanded blastocysts, while embryos transferred after vitrification and warming were predominantly expanded blastocysts. For vitrification, embryos were loaded into straws containing PBS (Invitrogen) with glycerol, ethylene glycol and FCS, adjacent to two fractions of galactose solution (Kaidi et al 2001). Embryos were warmed for 5 s in air and 10 s in a water bath at 30 8C.…”
Section: Embryo Transfer (Et)mentioning
confidence: 99%